2018
DOI: 10.14715/cmb/2018.64.14.2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic and maintenance regimens of vitamin D3 supplementation in healthy adults: A systematic review

Abstract: Studies carried out assessing the effect of different doses of cholecalciferol (vitamin D3) on correcting serum 25-hydroxyvitamin D deficiency in healthy adults are limited and review studies are lacking. Moreover, the maintenance dose and its duration offered by these few studies are inconsistent. We performed a systematic review of randomized clinical controlled trials (RCTs) that assessed the effect of different doses of vitamin D3 on serum 25(OH)D in healthy adults. PubMed database was searched from 2010 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
(46 reference statements)
1
5
0
2
Order By: Relevance
“…Furthermore, the massive monthly or bi-monthly oral dose was more convenient and was the best dose to maintain the levels relatively close to the previously optimized therapeutic levels in almost all patients year-round. Our results are consistent with a recent study that showed 50.000 IU vitamin D 3 bimonthly is required to maintain longterm sufficient 25(OH)D levels (Hassan, Hozayen, Alotaibi, & Tayem, 2018;Khawaja et al, 2017). Our results regarding the effectiveness of the larger bolus maintenance dose of 50.000 IU bimonthly in maintaining optimal serum 25(OH) D concentrations and even in some patients to ≥ 75 nmol/l, was inconsistent with other study that showed a higher monthly oral dose of 100.000 IU vitamin D for six months was more effective than a monthly dose of 50.000 IU in achieving serum-25(OH) D≥75 nmol/l (Mazahery, Stonehouse, & von Hurst, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the massive monthly or bi-monthly oral dose was more convenient and was the best dose to maintain the levels relatively close to the previously optimized therapeutic levels in almost all patients year-round. Our results are consistent with a recent study that showed 50.000 IU vitamin D 3 bimonthly is required to maintain longterm sufficient 25(OH)D levels (Hassan, Hozayen, Alotaibi, & Tayem, 2018;Khawaja et al, 2017). Our results regarding the effectiveness of the larger bolus maintenance dose of 50.000 IU bimonthly in maintaining optimal serum 25(OH) D concentrations and even in some patients to ≥ 75 nmol/l, was inconsistent with other study that showed a higher monthly oral dose of 100.000 IU vitamin D for six months was more effective than a monthly dose of 50.000 IU in achieving serum-25(OH) D≥75 nmol/l (Mazahery, Stonehouse, & von Hurst, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, it was found that the best regimen to supplement vitamin D in healthy adults consists of an initial large bolus dose of 600 000 IU monthly by intramuscular injections or a monthly oral dose of 200 000 IU or a weekly oral dose of 50 000 IU for 8 weeks, followed by a maintenance dose of 50 000 IU monthly or bimonthly. 51 The precise pathophysiology of IBS is not well-understood. It is hypothesized to involve interactions at the level of the gut microbiome, alterations in intestinal permeability, gut immunity, visceral sensation, and brain-gut interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to avoid adverse effects of vitamin D, the recommended dietary allowance of vitamin D is approximately 600 IU/day, with an upper limit of 4000 IU/day. Additionally, it was found that the best regimen to supplement vitamin D in healthy adults consists of an initial large bolus dose of 600 000 IU monthly by intramuscular injections or a monthly oral dose of 200 000 IU or a weekly oral dose of 50 000 IU for 8 weeks, followed by a maintenance dose of 50 000 IU monthly or bimonthly 51 …”
Section: Discussionmentioning
confidence: 99%
“…• Лечение дефицита витамина D рекомендуется препаратом колекальциферола** при установленном его дефиците (Таблица 8) и назначается курсом в лечебных дозах с последующим переводом на профилактическую терапию (Таблица 9) [237][238][239][240][241][242][243][244].…”
Section: витамин D и кальцийunclassified
“…Другой объединенный анализ 68 500 пациентов, получавших только колекальциферол**, не показал снижения риска переломов. Но комбинация препаратов кальция с колекальциферолом** снижала риск всех переломов на 12% (p = 0,025), переломов бедренной кости -на 26% (p = 0,005) [239].…”
Section: уровень убедительности рекомендаций а (уровень достоверности доказательств -1)unclassified